Parenting styles, self-efficacy, emotional intelligence and academic achievement in medical students - Qamar, Tania; Majeed, Sana (Pakistan Journal of Physiology, 2020)
Background: Academic achievement is the main concern of teachers, college consultants, and parents of students. The objective of this study was to observe the relationship between parenting styles, self-efficacy, emotional intelligence and academic achievement in medical students. Methods: Parenting style scale, generalized self-efficacy scale, emotional intelligence scale, and academic locus of control scale were used to measure variables under study. Data was collected from medical students of Lahore. Results: Correlational analysis showed highly significant positive association between parenting styles, self-efficacy, emotional intelligence and academic achievement in medical students. Regression analysis showed significant prediction between emotional intelligence and academic achievements. Moderation analysis showed self-efficacy was significant moderator between authoritarian parenting style and academic achievement. Conclusion: Medical students who have positive parenting styles, have high self-efficacy and emotional intelligence which leads them towards high academic achievement. Pak J Physiol 2020;16(2):59?61